Production of university patents: analysis in the states of Minas Gerais and Alagoas (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The aim of this study is to analyze the granting and patenting of patent applications at the Universidade Federal de Minas Gerais and Universidade Federal de Alagoas. It is characterized as descriptive, with a quantitative approach for data collection and analysis. The research universe includes patents filed and granted to universities in the database of the National Institute of Intellectual Property. The time frame covers the years 2000 to 2023. The data shows that there is a greater number of ungranted patents and a predominance of invention patents at the two universities.
Keywords: patent; patent document; scientific policy; innovation